Heterogeneous copper concentrations in cancerous human prostate tissues. Issue 14 (27th May 2015) - Denoyer, Delphine; Clatworthy, Sharnel A.S.; Masaldan, Shashank; Meggyesy, Peter M.; Cater, Michael A.
<x xml:space="preserve">Abstract</x> Background Therapeutics that target copper for the treatment of prostate cancer are being evaluated in human clinical trials. Elevated intracellular copper is considered to sensitize prostate cancer cells to certain copper‐coordination compounds, especially those with ionophoric properties. While there is compelling in vitro evidence that prostate cancer cells accumulate intracellular copper, a corresponding status for copper in patient tissues has not been corroborated. We therefore established whether copper concentrations increase in cancerous prostate tissues, and in sera, in patients throughout disease progression. Methods Human prostate tissue samples were obtained from patient prostatectomies (n = 28), and together with patient‐matched sera, were analyzed for copper content by inductively coupled plasma mass spectrometry. Results When grouped together, cancerous prostate tissues exhibiting moderate disease severity (Gleason Score 7) (n = 10) had 1.6‐fold more copper than age‐matched normal tissues (n = 10) (P < 0.05). Those with more aggressive disease (Gleason Score 9) (n = 8) had 1.8‐fold more copper (P < 0.05). In both disease stages however, the copper concentrations between individual samples were rather variable (0.55–3.02 μg/g), with many clearly within the normal range (0.52–1.28 μg/g). Additionally, we found that there was no change in serum copper concentrations in patients with either moderate or aggressive prostate cancer (Gleason Score 7 or 9), compared with reference intervals and to age‐matched controls. Conclusions The heterogeneous nature of copper concentrations in cancerous prostate tissues, suggest that a small subset of patients may respond to treatments that target elevated intratumoral copper. Therefore, such approaches would likely require personalized treatment strategies. Prostate 75:1510–1517, 2015. © 2015 Wiley Periodicals, Inc.